ปัจจัยจูงใจในการเลือกอาชีพรับราชการ ก่อนและหลังการประกาศใช้พระราชบัญญัติ ระเบียบข้าราชการพลเรือน พ.ศ. 2551: กรณีศึกษาสำนักงานคณะกรรมการ การศึกษาขั้นพื้นฐาน กระทรวงศึกษาธิการ - ทรัพย์มาก อภิณัฏฐ์; ไวทย์เลิศศักดิ์ (ยาบุชิตะ) เนตรนภา (Journal of Business, Innovation and Sustainability (JBIS), 2016)
งานวิจัยนี้ศึกษาว่าอะไรคือปัจจัยจูงใจให้คนเลือกอาชีพรับราชการ โดยแบ่งเป็น 3 ด้าน ได้แก่ ปัจจัยด้านภูมิหลัง ปัจจัยด้านครอบครัว และปัจจัยจูงใจในการเลือกอาชีพ และการแก้ไขพระราชบัญญัติฯ นี้มีส่วนสนับสนุนให้คนรุ่นใหม่สนใจเลือกอาชีพรับราชการจริงหรือไม่ โดยการสำรวจความคิดเห็นโดยใช้แบบสอบถามกับบุคลากรสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน กระทรวงศึกษาธิการ จำนวน 250 คน ซึ่งแบ่งเป็น 2 กลุ่ม คือ กลุ่มเข้ารับราชการก่อนและหลังปี 2551 ผลการวิจัยพบว่า ปัจจัยด้านภูมิหลังไม่แตกต่างระหว่าง 2 กลุ่ม ส่วนปัจจัยด้านครอบครัวพบว่าประมาณ 1 ใน 4 ของทั้ง 2 กลุ่มมีบิดาหรือมารดาประกอบอาชีพรับราชการ แต่ส่วนมากมาจากครอบครัวที่บิดาหรือมารดาประกอบอาชีพอิสระหรืออื่นๆ ผลการวิเคราะห์สถิติถดถอยพหุคูณพบว่า กลุ่มเข้ารับราชการก่อนปี 2551 เลือกด้วย 2 เหตุผล คือ ความมั่นคงในงาน และโอกาสแสดงความรู้ความสามารถและพัฒนาตนเอง ส่วนกลุ่มเข้ารับราชการหลังปี 2551 เลือกด้วย 2 เหตุผล คือ ความมั่นคงในงาน และสิ่งแวดล้อมในการทำงาน ทั้งนี้พนักงานทั้ง 2 กลุ่มเห็นว่างานราชการเป็นที่ได้รับการยอมรับและมีเกียรติ ดังนั้นนอกจากปัจจัยจูงใจภายนอกแล้ว หน่วยงานที่เกี่ยวข้องควรให้ความสำคัญกับการสร้างแรงจูงใจจิตสาธารณะกับคนรุ่นใหม่ และปรับปรุงภาพลักษณ์ที่ดีน่ายกย่องชื่นชมของงานข้าราชการด้วย Motivational Factors Influencing Civil Servants as a Career Choice before and after the Amendment of the Civil Service Act B.E. 2551: A Case Study of the Office of the Basic Education Commission, Ministry of Education This research aims to study what the motivational factors influencing people to choose civil servant careers are, which are divided into three factors: individual background, family background, and factors influencing occupational career choice, whether the amendment of the Civil Service Act in 2008 has contributed to encouraging young people to choose civil servant careers. The survey questionnaire was used with 250 staff members of the Office of the Basic Education Commission, Ministry of Education, divided into two groups: those who became civil servants before 2008, and those who became civil servants after 2008. The research found that individual backgrounds did not differ between the two groups. For the family background factors, it was found that about one in four of the two groups had either father or mother working in the civil service, but most of them came from families in which the parents were self-employed and others. The results of the multiple regression analysis found that the group that entered the civil service before 2008 chose their career based on two reasons: job security, and opportunity to demonstrate knowledge and skills and opportunity for self-development. On the other hand, the group that entered the civil service after 2008 chose their career based on two reasons: job security and working environment. Besides, both groups agreed that government employees were highly recognized and honored. Therefore, in addition to external incentives, the relevant authorities should also focus on grooming public service motivation among young generations, and improve the image of government officials. DOI: http://dx.doi.org/10.14456/becj.2016.8